Targeting an adhesion molecule to prevent brain colonization of lung cancer - Karreman, Matthia A.; Winkler, Frank (Neuro-Oncology, 2020)
One of the first steps of brain colonization (and thus a plausible target for preventive concepts) is the adhesion of circulating cancer cells to the brain microvascular endothelium. Here, an earlier study found that multiple adhesion molecules are upregulated in brain endothelial cells during micrometastatic seeding of breast cancer cells—most notably, activated leukocyte cell adhesion molecule (ALCAM), but also many others.5 Specifically, the inhibition of ALCAM by short in vitro incubation of breast cancer cells with an ALCAM-blocking antibody reduced the number of brain metastases that later formed in a mouse model, which speaks for a brain metastasis preventive effect.
Gesehen am 15.01.2021